A Facile Access to Piperidine Derivatives via Copper(I)-Catalyzed 1,3-Dipolar [6+3] Cycloadditions of Azomethine Ylides with Fulvenes - Tao, Hai-Yan; Wang, Chun-Jiang (Synlett, 2014)
Enantioenriched heterocyclic piperidines are important structural motifs present in numerous natural products and biologically active molecules. This article outlines our recent efforts to develop a straightforward access to highly functionalized piperidine derivatives with multiple stereogenic centers, in good yields and excellent stereoselectivities, via copper(I)/TF-BiphamPhos-catalyzed asymmetric 1,3-dipolar [6+3] cycloadditions of azomethine ylides with fulvenes.
Keywords: asymmetric catalysis; 1,3-dipolar cycloaddition; azomethine ylides; fulvenes; piperidines